Putting banana-coffee intercropping research into action - Ekong, J. (2015)
Research of the International Institute of Tropical Agriculture (IITA) and its partners shows that growing coffee and banana together is generating >50% more income for smallholder farmers and can help them cope with the effects of climate change. However, turning research into action on the ground requires effective dialogue and communication between researchers and policy makers. This study looks at how well informed government bodies, private sector and non-profit actors were of IITA’s research and to what extent the practice has been adopted.